Capital Formation and Argentina's Price-Cost Structure: A Reply - Hayn, Rolf (The Review of Economics and Statistics, 1964)
I appreciate the preceding comments. Beyond pointing out that careful reading of my note will show that I did not pretend to explain fully Argentina's postwar rate of capital formation, I would like to remark briefly on three matters. First, I seem to have been misunderstood. Since I did not mean to imply that the proportion of private saving, in the national income declined. I merely stated that, while certain conditions favored the use of savings for purposes other than fixed capital formation, it is also probable that the investment equivalent of the propensity to save declined. This could occur while the propensity to save out of current income remained constant or even increased. I based my conclusion on the rise in the share of wages in the national income1 and on a change in the price structure favoring lower income consumers in particular. Second, I do not think that conclusions regarding the marginal efficiency of capital can be drawn from the information given by Schwartz. His calculations, based solely on the capitalization of companies registered with the Buenos Aires stock exchange, suggest that the profitability of some companies increased. Yet, it may well have declined for the economy as a whole. Indeed, prices on the Buenos Aires stock exchange, after rising sharply until 1948, fell and, notwithstanding the violent inflation, had not reattained their 1948 level by 1958.2 Nor can pressure to import machinery be taken as evidence that the marginal efficiency of capital in general was high. Actually, imports of capital goodsbut not of raw material and intermediate partsaveraged less in the 1950's (1950-1958) than during 1935-1939 and 19461949, and investors had to be satisfied to a greater extent than they may have wished with locally produced capital goods.3 Third, Schwartz suggests that the investment consumption goods price ratio declined after 1949. This is correct, but the ratio by no means returned to the prewar level. Furthermore, following the 1955 and subsequent devaluations, import and investment prices rose substantially in relation to domestic and consumption prices respectively.4 In Table 1 of the note which is the subject of this discussion, I merely showed two averages one for 1946-1949, the other for 1950-1958-of the relationship between investment and consumption goods prices. I felt that this was enough to point out the new price relationships established during the 1940's and essentially maintained during the 1950's. In my judgment, the movement of the indices is of such magnitude that, notwithstanding the limitations inherent in them, they point to a substantial change in the price relationships between economic sectors. Interestingly, recent studies tend to confirm this conclusion. In 1960 and 1962, investment prices were higher in relation to consumption prices in Argentina than in other Latin American countries.5 I feel that such developments merit attention because of the effects they may have, not only on resource allocation, but on saving and capital formation in general. * The writer is a member of the United Nations Secretariat. Neither the opinions expressed here nor in the original article-written before he joined the United Nationsnecessarily reflect those of that organization. 1 Schwartz's point concerning social security taxes is correct. However, data excluding social security taxes also show an increase in the wage share for all sectors for the years 1946 to 1955 inclusive, for which the data are available to me. See United Nations, Economic Commission for Latin America, El Desarrollo Econo'mico de la Argentina, Anexo (mimeographed, 1958), 190, 191. 2 Bolsa de Comercio de Buenos Aires, Anuario Estadistico. 'R. Hayn, Inflaci6n, Formaci6n de Capital y Balance de Pagos de la Argentina, 1940-1958, Revista de Economia y Estadistica (Cordoba, Argentina, 1962), No. 2 (esp. Table 4). 'Ibid., (esp. Table 9). 5See footnote 1 in the note under discussion and United Nations, Economic Commission for Latin America, A Measurement of Price Levels and the Purchasing Power of Currencies in Latin America, 1960-1962 (mimeographed, March, 1963).